PENGARUH KECERDASAN INTERPERSONAL TERHADAP HASIL BELAJAR MATEMATIKA MATERI PECAHAN SISWA KELAS IV SD NEGERI LAMPER LOR SEMARANG - Bella Chesita Litahayu; Duwi Nuvitalia; Husni Wakhyudin (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2024)
This research aims to determine the effect of interpersonal intelligence on mathematics learning outcomes in fourth grade students' fraction material in SD Negeri Lamper Lor Semarang. This research uses quantitative methods with a correlational research design. The research sample consisted of fourth grade students in one of the elementary schools selected randomly. Data collection was carried out through pretest and posttest to determine the mathematics learning outcomes of students who have interpersonal intelligence. The data analysis technique uses simple regression analysis to test the influence of interpersonal intelligence on learning outcomes. The results of data analysis obtained through statistical tests, such as simple correlation and regression tests, show that there is a relationship between interpersonal intelligence and mathematics learning outcomes in fractions. Based on the correlation coefficient value of 0.732 with a significance level of 0.05, it was found that there is a significant influence between interpersonal intelligence on students' mathematics learning outcomes in fractions. This shows that the better the students' interpersonal intelligence, the better their mathematics learning outcomes in fractions material. The conclusion of this research is that interpersonal intelligence is an important factor that can influence student learning outcomes in mathematics subjects, especially fractions. Thus, teachers are expected to be able to develop learning strategies that support interactions between students to improve their interpersonal intelligence and learning outcomes. Keywords: Interpersonal Intelligence, Mathematics, Fractions and Learning Results